GW24-e0422 Myocardial Infarction Worsens the Podocyte Injury and Albuminuria in Potential Kidney Disease Rats probably via local hemodynamics-immunity way. (1st October 2013) - Zhifeng, Dong; Zhu, Wei; Wu, Penglong; Xin, Ping; Li, Yongguang; Li, Yapeng; Li, Shuai; Wei, Meng
Abstract : Objectives: Amounts of evidence demonstrated increased deterioration of renal function after chronic heart failure (CHF), particularly in patients who already had potential impairment such as diabetic nephropathy. Numberous studies suggested that the inflammation after abnormal renal hemodynamics played important roles in this interaction. Due to the inseparable relation between immunity and inflammation, we hypothesised that the aberrance of renal cellular, humoral immunity were also involved in this progression, and rho-kinase inhibitor (fasudil) which was thought to improve the renal vascular function would improve it. Methods: There are 8 rat groups in this study: 1. Ctr (n = 12): Sprague-Dawley (SD) rats with sham myocardial infarction (MI) operation then treated with vehicle for 3 months; 2. MI (n = 12): SD rats with surgically induced MI then treated with vehicle for 3months; 3. DB (n = 11): STZ-induced type 1 diabetic rats (16ws) with sham MI operation then treated with vehicle for 3months; 4. DB + MI (n = 11): STZ-induced type 1 diabetic rats (16ws) with MI operation then treated with vehicle for 3months; 5. DB + MI + Fas (n = 11): STZ-induced type 1 diabetic rats (16ws) with MI operation then treated with fasudil for 3months; 6. UNX (n = 11): SD rats underwent unilateral nephrectomy (UNX, 2ws) then treated with vehicle for 3 months; 7. UNX + MI (n = 11): UNX rats (2ws) underwent MI operation then treated with vehicle for 3 months; 8. UNX + MI + Fas (n = 11): UNX rats (2ws) underwent MI operation then treated with fasudil for 3 months. Renal hemodynamics/vascular reactivity were evaluated with DMT multi wire myograph system. The parameters of cellular, humoral immunity were evaluated with flow cytometry analysis, electron microscopy, Immunofluorescence and Immunohistochemistry. In addition the marker of glomerular podocyte injury such as desmin, nephrin were observed with Immunohistochemistry. Results: Compared with their sham-operation groups (DB, UNX), two operation groups (DB + MI, UNX + MI) showed: 1. significantly decreased renal reperfusion pressure (RPR) and increased vasoconstriction of renal interlobular arteries; 2. significantly increased infiltration of monocytes and the proportion of CD3+ cell, CD4+ T cells, producing-IFN-γ, IL-17, IL-4 CD4+ T cell and regulatory T cell, the deposition of immune complex (IgG) and complement C4 in glomeruli. 3. significantly aberrant albuminuria and the marker of glomerular podocyte injury such as desmin and nephrin. Two treated groups (DB + MI + Fas, UNX + MI + Fas) showed the improved parameters of hemodynamics/vascular reactivity, albuminuria and glomerular podocyte injury in varying degrees. At last the proportion of renal CD Conclusions: In this study, post-MI CHF significantly deteriorated the renal function and remodelling in potential renal injury rats (DB or UNX). They were accompanied with the aberrated renal hemodynamics/vascular reactivity and renal immune system. Rho-kinase inhibitor fasudil prevented the aberration of them and the deterioration of renal function, providing new insight into the treatment of cardiorenal syndrome.